Sociological Study of Puritanism Reasoning and Strengthening of Religious Inclusivity Attitude in the Endemic Era - Ahyar , Muhammad; Murdan (Indonesian Journal of Islamic Literature and Muslim Society, 2022)
Shock thinking and the attitude of claiming a single truth that leads to an attitude of social exclusivity is often the main trigger for the emergence of acts of intolerance in a plural, plural, especially multicultural society such as the Indonesian nation. This intolerance often arises from religious groups who shout loudly about religious puritanism. This puritanism and religious intolerance also spread in the Pandemic era, so it can muddy and complicate the handling of COVID-19 led by the Government of the Republic of Indonesia. After almost three years of dealing with the pandemic situation, the Indonesian people are preparing, staring, and supporting the Endemic era. Observing this Enddemic era, the Indonesian nation as a multicultural society really needs a moderate religious attitude so that the unity, unity, and integrity of the nation can be sustained, sustainable, and maintained. In this regard, this article will present discussion material on sociological studies on the strengthening of puritanism in the Pandemic era, and strengthen religious moderation in welcoming a new era called the Enddemic era.